2021
DOI: 10.3390/jcm10184209
|View full text |Cite
|
Sign up to set email alerts
|

“Lessons Learned” Preventing Recurrent Ischemic Strokes through Secondary Prevention Programs: A Systematic Review

Abstract: Recurrent ischemic strokes are a cause of significant healthcare burdens globally. Patients with uncontrolled vascular risk factors are more likely to develop recurrent ischemic strokes. This study aims to compile information gained from current secondary prevention programs. A pre-defined literature search strategy was applied to PubMed, SCOPUS, CINAHL, and Google Scholar databases, and studies from 1997 to 2020 were evaluated for quality, study aims, and outcomes. The search produced 1175 articles (1092 afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Indeed, our findings support the idea that access to primary care providers and inclusive healthcare (supportive of stroke recovery) is important. However, based on the work of others, without a patient-centered and culturally sensitive approach considering the SDoH that may contribute to disparities in stroke care, we will likely only have limited success [ 8 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our findings support the idea that access to primary care providers and inclusive healthcare (supportive of stroke recovery) is important. However, based on the work of others, without a patient-centered and culturally sensitive approach considering the SDoH that may contribute to disparities in stroke care, we will likely only have limited success [ 8 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To make a difference, programs need to be tailored to the requirements of the underserved and/or racialized patient population, and to be sustainable, these patient-focused solutions should make the best use of available resources and personnel [ 12 ]. Ultimately, if access to basic health care is not established, targeting underlying risk factors such as diabetes and hypertension are not sufficient to make headway in stroke prevention [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of programs designed to improve secondary stroke prevention, a minority of studies had persistent effects on successful TOC and stroke prevention, and these mostly involved interventions focused on reinforcing adherence to a care plan. 16 More recently, a randomized trial focused on effective TOC showed that the intervention was inconsistently implemented, with no effect on functional outcome or readmission. 17,18 Some explanations proposed for this negative result include that hospitals had difficulty sustaining the intervention, there was significant loss to follow-up, and outcome measures may have been insensitive in a milder stroke population.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled study showed that both face-to-face and telehealth education programs resulted in significant improvements in health behaviors related to physical activity, nutrition, low-salt diets, and medication adherence. Additionally, the intervention group exhibited decreased systolic BP and cholesterol levels [15,16]. Another similar study using a randomized controlled design found that a web-based stroke education program led to significant increases in exercise, reduced consumption of salty foods, increased intake of fruits and vegetables, enhanced sense of control, improved health motivation, and improved caregiver mastery.…”
Section: Introductionmentioning
confidence: 87%